Management Coach at Apacmandiri Football Academy - Muhammad Syifa'ul Khakim; Harry Pramono; Tri Rustiadi (JUARA : Jurnal Olahraga, 2022)
The purpose of this research is to find out how 1) the program; 2) income and expenses; 3) improving the ability of trainers; 4) the trainer recruitment process; 5) the welfare of the trainers using a qualitative research approach using the CIPP evaluation (context, input, process, product). Data collection techniques through interviews, observation and documentation. The subjects of this research include administrators, coaches and athletes. The data validity technique used 1) Observation; 2) In-depth interviews; 3) Documentation in data collection; 4) Drawing conclusions. In this study, the CIPP evaluation model will provide an overview of the management functions used at Apacmandiri Football Academy CIPP itself is used for evaluation based on the aspects that have been implemented. Research results and conclusions 1) The program in the management of independent trainers has been running and is organized with the existing provisions; 2) Income and expenses for academy needs have been running well, but not all of the facilities for trainer needs have been realized; 3) The improvement of the trainer's ability has been fulfilled using the trainer who has the highest license providing teaching to the trainer licensed under him, but there are still shortcomings, namely material support for improving the trainer's ability; 4) the recruitment process already has a standard set by the management and has been running well by the desired needs; 5) the welfare of their trainers is satisfied with what is currently available, and the distribution has been carried out in a well-organized manner.